2020
DOI: 10.3390/su122410605
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity and Risk Perception Explain Participation in the Swiss Youth Climate Strikes

Abstract: Since late 2018, young people around the world have united to demand greater action on climate change. Aside from their stated concerns and demands, however, very little is known about why young people have been joining this growing movement. Using a large sample (N = 4057) of people in Switzerland aged between 14 and 25, we show that social identity is most strongly associated with participation, followed by beliefs about the effectiveness of youth strikes, level of education, and worry about climate change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 91 publications
1
26
1
Order By: Relevance
“…Our results suggest that protesters who committed to the weekly climate strikes and signaled their engagement through Facebook events were mainly driven by their concerns about climate change. The importance of issue involvement, and concern specifically, is in accordance with other studies focusing on the 2019 climate protests [89,109], as well as with general understandings about issue publics [86]. Somewhat unexpectedly, however, none of the included political efficacies were associated with belonging to the protester class.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results suggest that protesters who committed to the weekly climate strikes and signaled their engagement through Facebook events were mainly driven by their concerns about climate change. The importance of issue involvement, and concern specifically, is in accordance with other studies focusing on the 2019 climate protests [89,109], as well as with general understandings about issue publics [86]. Somewhat unexpectedly, however, none of the included political efficacies were associated with belonging to the protester class.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, Roser-Renouf et al [87] showed how climate-related issue involvement, in terms of environmental concern and personal importance, was associated with both opinion leadership and offline climate activism. Similar studies indicated how specific environmental concerns are predictive of offline climate activism [88], including participation in the worldwide climate strikes [89].…”
Section: Issue Involvementmentioning
confidence: 87%
“…Following the pilot, larger studies in this area have had success engaging participants via schools (see, for example, Brügger et al, 2020;Harker-Schuch et al, 2020). For this study, several jurisdictions were approached to access public schools for survey and focus group participation, with application processes spanning from mid-2019 to early-2020.…”
Section: Survey Methodsmentioning
confidence: 99%
“…This model has been used by scholars to delve deeper into motivators of young School Strike attendees. For example, Brügger et al (2020) integrate the SIMCA to explore Strike motivations of over 4,000 Swiss youth aged 14-25. Their study found that social identity (the extent to which participants associate with other Strikers) as well as students risk perception of climate change were key factors in predicting engagement with the School Strike movement.…”
Section: Social Movements and The School Strikementioning
confidence: 99%
“…The current study advances the literature on collective action and protest participation in several ways. First, it provides some of the first empirical evidence on the motives for participation in the Fridays for Future strikes, one of the largest environmental social movements to date (for other studies on the climate strikes see: [ 16 20 ]. Second, it adds to the current literature on climate protest participation due to its novel approach of investigating the drivers of both participation and non-participation.…”
Section: Introductionmentioning
confidence: 99%